Acceptance of pharmaceutical cannabis substitution by cannabis using patients with schizophrenia - Jan van Amsterdam; Jojanneke Vervloet; Gerdien de Weert; Victor J. A. Buwalda; Anna E. Goudriaan; Wim van den Brink (BMC, 2018)
Abstract Background Cannabis-smoking patients with a psychotic disorder have poorer disease outcomes than non-cannabis-smoking patients with poorest outcomes in patients smoking high-potency cannabis (HPC) containing high Δ9-tetrahydrocannabinol (THC) and low cannabidiol (CBD). Quitting cannabis smoking or substitution of HPC by cannabis variants containing less THC and/or more CBD may benefit these patients. The present study explores whether daily HPC-smoking patients with schizophrenia accept smoking such variants. Methods Twelve male patients were asked to smoke on six different occasions one joint: on two occasions, the cannabis they routinely smoke (HPC; not blind), and blind in random order; on two occasions, cannabis containing low THC and no CBD; and on two occasions, cannabis containing low THC and high CBD. Results Both substitute variants were appreciated, but patients preferred the HPC they usually smoked. The effect of the low THC/high CBD variant was reported by 32% to be too short and by 36% to be not strong enough, whereas this was reported by 5% and 64%, respectively, for the low THC cannabis variant. Conclusions Based on these findings, a larger and longer study on the efficacy of cannabis substitution treatment in HPC-smoking patients with schizophrenia seems feasible and should be considered. Trial registration 2014-005540-17NL. Registered 22 October 2014, 2014-005540-17NL 20141215 CTA.xml